Registration of 17 Sorghum Pollinator Germplasm Lines Resistant to Acetolactate Synthase (ALS)–Inhibitor Herbicides. Issue 2 (28th March 2019) - Tesso, Tesfaye; Gobena, Dereje Dugassa; Perumal, Ramasamy; Bean, Scott; Wilson, Jeffery; Little, Christopher R.
Abstract : Seventeen sorghum [ Sorghum bicolor (L.) Moench] pollinator lines carrying the homozygous resistance gene to the acetolactate synthase (ALS)‐inhibitor herbicides were developed and released by the Kansas Agricultural Experiment Station, Manhattan, KS in 2014. The resistance gene was introduced from shattercane, a wild relative of sorghum, first discovered in Kansas. These lines—PR11/12‐806 (Reg. No. GP‐867, PI 689022), PR11/12‐807 (Reg. No. GP‐868, PI 689023), PR11/12‐816 (Reg. No. GP‐869, PI 689024); PR11/12‐821 (Reg. No. GP‐870, PI 689025), PR11/12‐824 (Reg. No. GP‐871, PI 689026), PR11/12‐828 (Reg. No. GP‐872, PI 689027), PR11/12‐829 (Reg. No. GP‐873, PI 689028), PR11/12‐830 (Reg. No. GP‐874, PI 689029), PR11/12‐836 (Reg. No. GP‐875, PI 689030), PR11/12‐838 (Reg. No. GP‐876, PI 689031), PR11/12‐867 (Reg. No. GP‐877, PI 689032), PR11/12‐873 (Reg. No. GP‐878, PI 689033), PR11/12‐903 (Reg. No. GP‐879, PI 689034), PR11/12‐925 (Reg. No. GP‐880, PI 689035), PR11/12‐928 (Reg. No. GP‐881, PI 689036), PR11/12‐930 (Reg. No. GP‐882, PI 689037), and PR11/12‐948 (Reg. No. GP‐883, PI 689022)—are of typical combine height, are photoperiod insensitive, and reach half‐bloom stage in 60 to 70 d after planting under Manhattan, KS, conditions. The seed color ranges from bright red to tan white. All lines restore fertility in A1 cytoplasm and have good combining ability for yield. These lines can be useful sources for breeding herbicide‐resistant pollinator lines or for direct use as pollinator parent in the production of ALS inhibitor herbicide–resistant hybrid seed.